2014
DOI: 10.2996/kmj/1404393894
|View full text |Cite
|
Sign up to set email alerts
|

Almost complete intersections and Stanley's conjecture

Abstract: Let K be a field and I a monomial ideal of the polynomial ring S = K[x 1 , . . . , xn]. We show that if either: 1) I is almost complete intersection, 2) I can be generated by less than four monomials; or 3) I is the Stanley-Reisner ideal of a locally complete intersection simplicial complex on [n], then Stanley's conjecture holds for S/I.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…The similar characterizations of being Buchsbaum and generalized Cohen-Macaulay were also studied by them. Minh and Trung in [12] proved that for simplicial complex ∆ with dim(∆) = 1, I (2) ∆ is Cohen-Macaulay if and only if diam(∆) ≤ 2, where diam(∆) denotes the diameter of ∆. We pursue this line of research further.…”
Section: Introductionmentioning
confidence: 89%
See 3 more Smart Citations
“…The similar characterizations of being Buchsbaum and generalized Cohen-Macaulay were also studied by them. Minh and Trung in [12] proved that for simplicial complex ∆ with dim(∆) = 1, I (2) ∆ is Cohen-Macaulay if and only if diam(∆) ≤ 2, where diam(∆) denotes the diameter of ∆. We pursue this line of research further.…”
Section: Introductionmentioning
confidence: 89%
“…Let ∆ be a 1-dimensional simplicial complex and I = I ∆ ⊂ S. Minh and Trung in [12] studied under which conditions S/I (2) and S/I 2 are Cohen-Macaulay. In this section we will give a characterization for the Cohen-Macaulayness of S/I (2) and S/I 2 in terms of the cleanness property.…”
Section: Second Symbolic Power and Cleannessmentioning
confidence: 99%
See 2 more Smart Citations
“…In a very recent paper [14], Bandari, Divaani-Aazar and Soleyman Jahan showed that if I S D KOEx 1 ; : : : ; x n is a monomial ideal generated by monomials u 1 ; u 2 ; : : : ; u t , then S=I is pretty clean (and hence satisfies Stanley's conjecture) if either: u 1 ; u 2 ; : : : ; u t is a filter-regular sequence, or d -sequence, or I is an almost complete intersection. In a very recent paper [14], Bandari, Divaani-Aazar and Soleyman Jahan showed that if I S D KOEx 1 ; : : : ; x n is a monomial ideal generated by monomials u 1 ; u 2 ; : : : ; u t , then S=I is pretty clean (and hence satisfies Stanley's conjecture) if either: u 1 ; u 2 ; : : : ; u t is a filter-regular sequence, or d -sequence, or I is an almost complete intersection.…”
Section: What Is Know About Stanley's Conjecture?mentioning
confidence: 99%